A study of the solutions of The Yang-Mills-Higgs theory. - Teh, Rosy Chooi Gim (Universiti Sains Malaysia, 2005)

(untitled)
In our project, we have constructed exact static multimonopole-antimonopole solutions and their anti-configurations of the SU(2) Yang-Mills-Higgs (YMH) field theory.